Using heart girth to determine weight in finishing pigs - C N Groesbeck; K R Lawrence; M G Young; Robert D Goodband; Joel M DeRouchey; Michael D Tokach; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
Heart girth and body weight were measured on 100 growing-finishing pigs (50 to 273 lb) at the KSU Swine Teaching and Research Center. Heart girth, in inches, was measured using a cloth measuring tape. The tape was placed directly behind the front legs and then wrapped around the heart girth and read directly behind the shoulders. Heart girth was strongly correlated (R2=0 .98) with body weight, with the following regression equation: pig weight = 10.1709 × Heart girth - 205.7492. The 95% confidence interval shows the projected weight to be ±10 lb of the actual weight of the pig. To validate our equation we weighed and measured heart girth on 40 pigs from a commercial breeding farm and a group of 165 pigs at the 2002 Swine Classic Youth Exposition. At the commercial breeding farm, the actual measured body weights fit within the 95% confidence interval from their projected weights, based on the regression equation. The average residual (difference between predicted and actual weight) of the 40 pigs was -0.70 lb with a range of ± 4 lb. The actual weights of pigs at the Swine Classic averaged 16 lb greater than their predicted body weights with a range of ±8.5 lb. The actual weights failed to fall within the 95% confidence interval for the developed regression equation. This was probably due to shrink during transportation to the show and limited feed and water. Heart girth as a means of determining body weight is a viable device for 4-Hers and producers, but it is important to use only on pigs with continuous access to feed and water.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Swine; Heart girth; Weight